2018
DOI: 10.1080/24734306.2018.1467532
|View full text |Cite
|
Sign up to set email alerts
|

Survival after severe methemoglobinemia secondary to sodium nitrate ingestion

Abstract: Sodium nitrate is used as a food preservative and color fixative. Sodium nitrate poisoning has occurred in the setting of well water contamination with nitrogenous waste runoff. Most clinically significant exposures result from improper labeling or unintentional use. We describe a case of severe methemoglobinemia associated with intentional sodium nitrate ingestion. A 23-year-old female presented to the emergency department (ED) for an intentional ingestion of sodium nitrate obtained from an online distributor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…[3] Methemoglobin levels >70% are lethal, but survival has been reported in more than 90% of cases. [ 5 , 7 ]…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[3] Methemoglobin levels >70% are lethal, but survival has been reported in more than 90% of cases. [ 5 , 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…The number of cases of sodium nitrite intoxication due to a suicidal attempt has increased. [ 4 , 5 ] A recent study conducted in Korea reported 14 autopsy cases from sodium nitrite poisoning from 2013 to 2019. Until 2017, there has been 1 autopsy every year, but it increased to 8 cases in 2018.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations